Biologically agglutinated eukaryotic microfossil from Cryogenian cap carbonates. Issue 4 (6th January 2017) - Moore, K. R.; Bosak, T.; Macdonald, F. A.; Lahr, D. J. G.; Newman, S.; Settens, C.; Pruss, S. B.
Abstract: Cryogenian cap carbonates that overlie Sturtian glacial deposits were formed during a post‐glacial transgression. Here, we describe microfossils from the Kakontwe Formation of Zambia and the Taishir Formation of Mongolia—both Cryogenian age, post‐Sturtian cap carbonates—and investigate processes involved in their formation and preservation. We compare microfossils from these two localities to an assemblage of well‐documented microfossils previously described in the post‐Sturtian Rasthof Formation of Namibia. Microfossils from both new localities have 10 ± 1 μm‐thick walls composed of carbonaceous matter and aluminosilicate minerals. Those found in the Kakontwe Formation are spherical or ovoid and 90 ± 5 μm to 200 ± 5 μm wide. Structures found in the Taishir Formation are mostly spherical, 50 ± 5 μm to 140 ± 5 μm wide, with distinct features such as blunt or concave edges. Chemical and mineralogical analyses show that the walled structures and the clay fraction extracted from the surrounding sediments are composed of clay minerals, especially muscovite and illite, as well as quartz, iron and titanium oxides, and some dolomite and feldspar. At each locality, the mineralogy of the microfossil walls matched that of the clay fractions of the surrounding sediment. The abundance of these minerals in the walled microfossils relative to the surrounding carbonate matrix and microbial laminae, and the presence of minerals that cannot precipitate from solution (titanium oxide and feldspar), suggests that the composition represents the original mineralogy of the structures. Furthermore, the consistency in mineralogy of both microfossils and sediments across the three basins, and the uniformity of size and shape among mineral grains in the fossil walls indicate that these organisms incorporated these minerals by primary biological agglutination. The discovery of new, mineral‐rich microfossil assemblages in microbially laminated and other fine‐grained facies of Cryogenian cap carbonates from multiple localities on different palaeocontinents demonstrates that agglutinating eukaryotes were widespread in carbonate‐dominated marine environments in the aftermath of the Sturtian glaciation.